Leguminous forage crops of different origin in Mediterranean environment - Maiorana M.; Convertini G.; Fornaro F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In a hilly area of Southern Italy (Apulian Murgia) the adaptation and productive capacities of a tropical legume, Lotononis (Lotononis bainesii L., cv. Miles) and a Spanish spontaneous alfalfa, Mielga (Medicago sativa L.) have been evaluated in comparison with an Italian alfalfa (Medicago sativa L., cv. Garisenda). All of the species were grown under dry conditions and submitted to two levels of phosphoric fertilizer (50 and 100 kg ha-1 of P2O5). The data obtained in the first two years of the trial (1996 and 1997) show that both Lotononis and Mielga grow well in an environment characterized by hot-dry climate and by soils with low fertility, supplying good productions of green forage and satisfactory contents of crude protein and neutrodetergent fibre. With reference to the effects of phosphorus doses, the best responses have been obtained with the application of 100 kg P2O5 ha-1, with differences almost always significant to analysis of variance.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)